In Silico Detection of Antimicrobial Resistance and Virulence Genes in Methicillin Resistant Staphylococcus aureus Clinical Isolates: A Comparative Genomics Approach - Muhammad Taufiq Hidayat; Endah Prayekti; Muhammad Afwan Romdloni; Seggaf Achmad Syah (Program Studi Pendidikan Biologi FKIP Unpatti, 2026)
Methicillin-resistant Staphylococcus aureus (MRSA) remains a formidable threat in both community and healthcare settings, thanks to its ability to evade β-lactam antibiotics and accumulate resistance to multiple drug classes. Here, we sequenced and compared the genomes of 13 recent clinical MRSA isolates alongside two well-characterized reference strains (N315 and NCTC 8325). By applying the ResFinder and VirulenceFinder pipelines, we rapidly cataloged each strain’s antibiotic resistance and virulence repertoire. Every MRSA isolate carried the hallmark mecA gene, and most also harbored blaZ, which encodes penicillinase. Resistance determinants for aminoglycosides (aac(6′)-Ie-aph(2″), aph(3′)-III), macrolides (erm(C), mph(C)), and chloramphenicol (cat variants) appeared in various combinations across the collection. On the virulence side, genes for α- and γ-hemolysins (hla, hlgABC) were universal, and nearly all strains possessed phage-encoded immune-evasion factors (sak, scn). The total count of virulence genes ranged from ten to fourteen per genome, peaking in two particularly gene-rich isolates. Our findings highlight the genetic diversity of MRSA, where multidrug resistance and a broad toxin arsenal coexist. Moreover, this study underscores the speed and reliability of in silico screening tools for antimicrobial-resistance surveillance and comparative genomics. Future work should integrate laboratory assays and patient data to link these genomic profiles to clinical outcomes.